Edukasi Interaktif Siswa SD Melalui Aplikasi ARJASS Pada Jajanan Sekolah untuk Pencegahan Stunting - irawati, Tri Novita; Nugraheni, Dyah Ayu; Rakhmawati, Dewi (Dedication : Jurnal Pengabdian Masyarakat, 2025)
The habit of consuming snacks that are low in nutrition and high in additives is a risk factor for stunting in school children. Lack of knowledge of nutritional content makes it difficult for students to choose healthy foods. This condition was also found at SD NU 02 Diponegoro Wuluhan Jember, where the majority of students bought snacks from street vendors with attractive appearance but minimal nutrition. This service program aims to increase students' knowledge through interactive education using ARJASS (Augmented Reality Healthy School Snacks). The activity was attended by 76 students in grades I–VI, including socialization, training in application use, practice, and evaluation through questionnaires and quizzes. The results show a high positive response: Application content 92%, accuracy 85%, display 97%. In addition, 80% of students obtained quiz scores >80, indicating a good increase in knowledge. AR technology has been proven to be effective, interesting and fun, so it has the potential to become a sustainable nutrition education strategy in preventing stunting from an early age.